The reaction (p)over-barp -> (Lambda)over-bar(c)(-)Lambda(+)(c) close to threshold - Haidenbauer, J.; Krein, Gastão Inácio [UNESP] (Elsevier B.V., 2010)
Predictions for the charm-production reaction (p) over barp -> (Lambda) over bar (-)(c)Lambda(+)(c) for energies near the threshold are presented. The calculations are performed in a meson-exchange framework in close analogy to our earlier study on (p) over barp -> (Lambda) over bar Lambda by connecting the two processes via SU(4) symmetry. The obtained (Lambda) over bar (-)(c)Lambda(+)(c) production cross sections are in the order of 1 to 7 mu b, i.e. a factor of around 10-70 smaller than the corresponding cross sections for (Lambda) over bar Lambda. However, they are 100 to 1000 times larger than predictions of other model calculations in the literature. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Charmed-baryon production; Proton-antiproton annihilation; Meson-exchange model; Quark model